Unveiling key genetic determinants of charcoal rot resistance in soybean via genome-wide association studies - Nataraj, Vennampally; Amrate, Pawan Kumar; Ratnaparkhe, Milind B.; Maranna, Shivakumar; Rajput, Laxman Singh; Agrawal, Nisha; Raghuvanshi, Rishiraj; Pathak, Kriti; Mandloi, Saloni; Mohare, Salikram; Naik K, Bhojaraja; Shrivastava, Manoj K.; et al. (Frontiers in Plant Science, 2025)
Charcoal rot is a soil- and seed-borne disease caused by a necrotrophic fungal pathogen—Macrophomina phaseolina. To understand the genetic architecture of resistance against it, a genome-wide association study (GWAS) was conducted based on a glasshouse experiment and a 3-year field experiment using 214 diverse soybean accessions. In a glasshouse experiment at the seedling stage, eight single-nucleotide polymorphisms (SNPs) were identified: one SNP each on chromosome (chr) 8 (S8_16817767), chr 10 (S10_52066337), chr 14 (S14_50857981), chr 15 (S15_32620059), chr 17 (S17_1689021), and chr 18 (S18_9413708), while two SNPs (S16_34569104 and S16_37878937) were located on chr 16. In the case of the field experiment at the reproductive stage, 10 SNPs were identified: 1 SNP each on chr 12 (S12_14977708), chr 14 (S14_51754926), and chr 16 (S16_33491560), 2 SNPs each were identified on chr 6 (S6_41109641 and S6_41863847) and chr 10 (S10_40644409 and S10_44768495), while 3 SNPs (S18_25004105, S18_55655188, and S18_56366541) were located on chr 18. The SNP S14_50857981 associated with seedling resistance and S14_51754926 associated with adult plant resistance are present within the 1-Mb region and will be of immense importance for charcoal rot resistance breeding. The putative candidate gene analysis for identified SNPs revealed 23 genes with annotations associated with defense response pathways. Three genes encoding an NB-ARC domain associated with defense response were present near S14_50857981. The genotype PI 159923 was found to be resistant under both field and glasshouse conditions, and it will be employed as a parent in breeding for high-yielding charcoal rot-resistant genotypes. Our study provides new insights into charcoal rot resistance in soybean, identifying key SNPs and genes that can aid future breeding programs for developing climate-resilient crops.